THE IMPORTANCE OF TPR TEACHING - Mamatqulov Shaxobiddin ("Conference on Universal Science Research 2023", 2023)
The earlier language learning starts, the higher the level of language acquisition. The natural nature of language learning in children, their strong imitation, the large number of children compared to adults is one of the main reasons for this. It should be noted that 6-7-year-old children do not understand the meaning of words, but memorize them mechanically. Teaching these children, a foreign language has its own method and methods. Because it affects all areas of the harmonious development of modern pedagogy, and consists of the search for non-existent methods and the necessary. It is for this reason that the article discusses the TPR method.